The ideology of Brazilian parties and presidents: a research note on coalitional presidentialism under stress - Zucco, C; Power, TJ (Cambridge University Press, 2024)
This research note contributes updated and extended point estimates of the ideological positions of Brazilian political parties and novel estimates of the positions of all presidents since redemocratization in 1985. Presidents and parties are jointly responsible for the operability of Brazil’s version of coalitional presidentialism. Locating these key political actors in a unidimensional left–right space over time reveals rising challenges to the institutional matrix, particularly since 2013. Ideological polarization among parties has sharply increased, presidents have become more distant from Congress, and the political center has become increasingly vacated. Coalitional presidentialism is being subjected to unprecedented ideological stress as President Luiz Inácio Lula da Silva begins his third term in office.